The Histone Demethylase IBM1 Positively Regulates Arabidopsis Immunity by Control of Defense Gene Expression - Chan, Ching; Zimmerli, Laurent (Frontiers in Plant Science, 2019)
Epigenetic modifications involve complex and sophisticated control over chromatin states and DNA methylation patterns, which are important for stress tolerance in plants. While the identification of epigenetic modulating enzymes keeps growing, such as MET1, for CG methylation; CMT3, DRM2, DRM3 for CHH methylation; and IBM1, SUVH4 for CHG methylation; the molecular roles of these regulators in specific physiological functions remain obscure. In a mutant screen, we identified IBM1 as a new player in plant immunity. The ibm1 mutants were hyper-susceptible to hemi-biotrophic bacteria Pseudomonas syringae. Accordingly, bacteria-induced up-regulation of PR1, PR2 and FRK1 defense markers was abolished in ibm1 mutants. Consistently, at the chromatin level, these defense marker genes showed enrichment of the inactivation mark, H3K9me2; while the activation mark H3K4me3 was reduced in ibm1 mutants. Immunoprecipitation of associated chromatin further demonstrated that IBM1 binds directly to the gene body of PR1, PR2 and FRK1. Taken together, these data suggest that IBM1 plays a critical role in modulating Arabidopsis immunity through direct regulation of defense gene expression. Notably, IBM1 maintains a permissive chromatin environment to ensure proper induction of defense genes under some biotic stress.